Convergência das normas e práticas contábeis brasileiras às normas internacionais e suas implicações no ensino superior em ciências contábeis - Gemaque, Licia Santos Buhaten (2010)
The growth of global markets, the enlargement of capital markets and the significant increase in acquisitions, mergers and acquisitions of companies around the world have led to a need for harmonization of standards and accounting practices. The process of harmonization will facilitate the comparability of financial statements between countries, improving the process of taking decisions and increasing foreign investment in countries. In this context, Brazil enacted the Law no. 11.638/07 and no. 11.941/09 in order to meet the convergence of international accounting standards and practices to Brazil. These changes in the Brazilian accounting legislation directly affects the teaching of science books, since the education of accounting needs to be appropriate for the new global reality. Therefore, the objective of this research is to analyse the implications of convergence of Brazilian accounting standards and practices to international standards in Higher Education in Accounting and either verify the modifications in the Brazilian science books curriculum, as by identifying the implemented actions in the way of renew the teachers grades and to prepare the graduates to the new reality.